INCLUSIVE GOVERNANCE AND THE RULE OF LAW: HUMAN RIGHTS PROTECTION IN THE POST-GLOBALIZATION ERA IN THE REVIEW OF THE HADITH - Mubarok, Aziz Al Ahmad Aly Syukron; Ahmadi, Alfarabi Shidqi; Damanhuri, Damanhuri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the concept of inclusive governance and the rule of law in protecting human rights in the post-globalization era through the perspective of the Hadith. The research employs a qualitative method with a normative-analytical approach, focusing on the thematic interpretation of selected Hadiths that emphasize justice, inclusivity, and legal supremacy. Data collection includes literature review and the analysis of classical and contemporary Islamic texts. The findings highlight that principles of inclusive governance and legal supremacy align with the core values of the Hadith, which advocate for justice, the prevention of oppression, and the protection of minority rights. The research reveals that integrating these principles into modern governance models can address socio-political inequalities and strengthen human rights protection. The study concludes that the Hadith offers valuable guidance for reimagining governance frameworks that are just, inclusive, and rooted in moral and ethical principles, making them adaptable to the challenges of the post-globalization era.